Three-dimensional kinematics and EMG of the lower limb of male and female athletes performing a single limb landing - Beaulieu, M.; Lamontagne, M. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of this study is to compare the time-frequency characteristic, the amplitude and the timing of recruitment of the EMG signal, as well as the three-dimensional kinematics, of the lower limb of female and male volleyball players performing a one-legged drop jump landing. Results showed that women landed with significantly higher peak knee abduction angles than men. Furthermore, peak activity of the semitendinosus, relative to initial contact (IC), occurred significantly sooner (prior to IC) for the female athletes than the male athletes (following IC). The male volleyball players' timing might be more protective to the ACL as the peak anterior tibio-femoral shear force is generated after 1C. In addition, no gender differences were found for median frequency of muscle activity prior to and following IC.